Implementation of Islamic Organizational Culture in Indonesian Islamic Rural Bank - Heriansyah, Heriansyah; Sitorus, Iwan Romadhan; Rahmat, Ihsan (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
Purpose: This study explains the internalization of Islam into the organizational culture in Islamic banks.Design/methodology: BPR Syariah Maslahat Dana Syariah Nusantara in Bengkulu City was appointed as a single case study. A semi-structured interview technique has been used, in addition to direct observation and several document collections such as bank profiles, meeting minutes, photos of activities, and monthly work recaps. All data were grouped, while interviews and observations were transcribed, coded, and categorized keywords.Findings: This article shows that the internalization of Islam in organizations is carried out simultaneously through written administrative regulations. The activities are congregational prayers at Zuhr time, reading several hadiths after prayer, weekly recitations in the office, reading Yasin’s letter every Friday morning, and monthly recitations carried out alternately at employees’ homes. In addition, several forms of Islamic values are also reflected in many practices: greeting and smiling to customers, speaking according to etiquette to coworkers, and wearing clothes that conform to Islamic standards.Practical implications: We have taken best practices from the implementation of Islamic organizational culture in banks and similar institutions. The culture and values can be modified according to the existing working procedures.Originality/Value: The conceptualization of Islamic organizational culture has been a topic of discussion. However, there is a dearth of documentation regarding best practices in Islamic banking. This study aims to provide insights into the adoption of effective practices at the organizational level within the Islamic banking sector.